The Effect of Exchange Rate Differences and Inventory Turnover on Profit Quality and Their Impact on Firm Value in the Covid-19 Pandemic Era - Arisma Dwi Astuti; Hari Setiyawati (CV. AFDIFAL MAJU BERKAH, 2023)
The pandemic caused by Covid-19 has had an impact on the sustainability of companies in the world one of which is that sales have decreased along with restrictions on international export trading activities. Covid-19 makes it difficult to maintain consistency in generating profits, this shows that the industrial sector has its own way of surviving amidst a pandemic storm that has hit all countries in the world. The aims of this study are: (1) to determine the effect exchange rate differences during the covid-19 pandemic on profit quality conditions, (2) knowing the effect of inventory turnover during the pandemic Covid-19 on the condition of profit quality, and (3) knowing the quality of earnings has an impact on company value during the Covid-19 pandemic. The method used is a quantitative research method, where the information provided can come from in-depth analysis of data collected first-hand, or from data that is already available. The population in this study were 41 companies in the industrial sector category listed on BE I, and 28 companies as the sample. Researchers in this study used secondary data collection techniques available on the Indonesian Stock Exchange during the study period. The results of the study show that (1) exchange rate differences have a significant positive effect on earnings quality during the Covid-19 pandemic. The increase in exchange rates during the Covid-19 pandemic made it profitable for companies to increase profits, (2) inventory turnover had a positive effect on profit quality during the Covid-19 pandemic, the company's financial performance was able to manage inventory turnover so that it was able to break down costs, provide input flows money comes in and increases profits which attract investors to invest in the industrial sector, and (3) profit quality has a positive effect on company value during the co-19 pandemic